Sediment Losses in Watersheds in the Western-Center Meso-Region Rio-grandense - krolow, Ivan Renato Cardoso; Rheinheimer, Danilo Dos Santos; Pellegrini, André; Alvarez, Jimmy Walter Rasche; krolow, Daniela da Rocha Vitória; Mohammed, Benkhelifa (Comunicata Scientiae, 2019)
The permanent monitoring of sediment losses in small-paired watersheds is still incipient, especially in what concerns the search for information that combines variables that are part of an open and dynamic system. In this sense, this work investigated sediment losses in watersheds in the Western Meso-region Rio-grandense from 07/2010 to 12/2012. The auxiliary variables were composed of rainfall, surface and base flow and kinetic energy – in comparison to the morphometry of each microbasin and its use – to the concentration of suspended sediments and total sediment loss. Statistical analysis of the data was based on descriptive statistics, taking into account the indicators of cumulative, average, standard deviation, standard error and variance, as well as regression analysis. The largest mild to smooth corrugate relief area of the smallest river basins is not sufficient to provide lower superficial runoff values. The increase in rainfall directly contributes to the increase in kinetic energy, and leads to greater sediment losses in both small hydrographic basins. The larger area occupied by natural water reservoirs contributes efficiently to the reduction of suspended sediment losses. The watershed with larger area is more susceptible to the triggering of erosive processes than to the smaller area, in 8 (2010), 6 (2011) and 4 (2012) times.